Adolescent health and subsequent risk of self-harm hospitalisation: a 15-year follow-up of the Young-HUNT cohort - Asbjørn Junker; Johan Håkon Bjørngaard; Ottar Bjerkeset (BMC, 2017)
Abstract Background Self-harm is associated with increased suicide risk, and constitutes a major challenge in adolescent mental healthcare. In the current study, we examined the association between different aspects of adolescent health and risk of later self-harm requiring hospital admission. Methods We linked baseline information from 13 to 19 year old participants (n = 8965) in the Norwegian Young-HUNT 1 study to patient records of self-harm hospitalisation during 15 years of follow-up. We used Cox regression to estimate risk factor hazard ratios (HR). Results Eighty-nine persons (71% female) were admitted to hospital because of self-harm. Intoxication/self-poisoning was the most frequent method (81%). Both mental (anxiety/depression, loneliness, being bullied) and somatic (epilepsy, migraine) health issues were associated with up to fourfold increased risk of self-harm-related hospital admission. Conclusions Several health issues during adolescence markedly increased the risk of later self-harm hospitalisation. Current findings should be incorporated in the strive to reduce self-harming and attempted suicides among young people.